On the Stability of DNA Origami Nanostructures in Low‐Magnesium Buffers. Issue 30 (19th June 2018) - Kielar, Charlotte; Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian
Abstract: DNA origami structures have great potential as functional platforms in various biomedical applications. Many applications, however, are incompatible with the high Mg 2+ concentrations commonly believed to be a prerequisite for maintaining DNA origami integrity. Herein, we investigate DNA origami stability in low‐Mg 2+ buffers. DNA origami stability is found to crucially depend on the availability of residual Mg 2+ ions for screening electrostatic repulsion. The presence of EDTA and phosphate ions may thus facilitate DNA origami denaturation by displacing Mg 2+ ions from the DNA backbone and reducing the strength of the Mg 2+ –DNA interaction, respectively. Most remarkably, these buffer dependencies are affected by DNA origami superstructure. However, by rationally selecting buffer components and considering superstructure‐dependent effects, the structural integrity of a given DNA origami nanostructure can be maintained in conventional buffers even at Mg 2+ concentrations in the low‐micromolar range. Abstract : The stability of DNA origami nanostructures in various Tris and phosphate‐based buffers was evaluated at residual Mg 2+ concentrations in the low‐micromolar range. DNA origami stability was found to be crucially affected by the presence of EDTA and phosphate ions that may displace bound Mg 2+ ions from the DNA backbone and reduce the strength of the Mg 2+ –DNA interaction, respectively. These effects furthermore depend on DNA origami superstructure.